Heterogeneity in exchange rate expectations: evidence on the chartist-fundamentalist approach - Lukas Menkhoff; Rafael R. Rebitzky; Michael Schröder (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper examines heterogeneity in exchange rate expectations. Whereas agents' heterogeneity is key in modern exchange rate models, evidence on determinants of heterogeneity is weak so far. Our sample, covering expectations from about 300 forecasters over 15 years, shows remarkable time variation in dispersion. Determinants of dispersion are consistent with the chartist-fundamentalist approach: misalignments of the exchange rate and exchange rate changes explain heterogeneity. The risk premium influences heterogeneity as well, but possible impacts from macroeconomic variables and exchange rate's volatility are dominated by the other determinants.
Keywords: F31; G14; 330; Exchange rate; heterogeneity; dispersion; chartists; fundamentalists; Wechselkurs; Erwartungstheorie; Wertpapieranalyse; Deutschland